Digital and other virtualities : renegotiating the image / Antony Bryant - Bryant, Antony
If virtuality is being celebrated as heralding a radically new era, rich with new possibilities and futures hitherto unimagined through cybernetics, networking and digitalizaton, such claims are also being viewed with deep scepticism and countered by renewed interest in the groundedness and referentiality of the concept of the index. In this transdisciplinary book, major artists, filmmakers, film theorists, philosophers, literary critics, information theorists and cultural analysts examine the twists and turns of the contesting terms of virtuality and indexicality in contemporary cultural theo.